1976
DOI: 10.1093/jn/106.6.802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluoride and Ethane-1-Hydroxy-1,1-Diphosphonate on Bone Metabolism in the Growing Chick

Abstract: White Leghorn cockerols were fed a semipurified diet (containing fluoride at 0 to 800 ppm) from the day of hatching. The birds were also injected daily with solutions containing ethane-1-hydroxy-1,1-diphosphonate (EHDP) at concentrations ranging from 5 to 20 mg as phosphorus/kg of body weight or isotonic saline. Changes in bone mineral composition and plasma Ca, Mg and F were determined as well as alterations in bone pyrophosphatase and the amounts of bone cyclic-3',5'-adenosine monophosphate (cAMP). Since die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The small net increase in calcium mass observed weekly during four weeks was the result of a 90% inhibition of mineralization. These data are consistent with previous findings [10][11][12][13].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The small net increase in calcium mass observed weekly during four weeks was the result of a 90% inhibition of mineralization. These data are consistent with previous findings [10][11][12][13].…”
Section: Discussionsupporting
confidence: 94%
“…In vivo EHDP has been used to study calcium metabolism. Early studies demonstrated that EHDP administration (5-20 mg/kg) can inhibit bone mineralization in various species: cat [6], dog [7], rat [7][8][9], and chick [10][11][12][13]. The effect of EHDP has been ascribed to a direct inhibition of EHDP at the mineralization site [4] and inhibition of vitamin D activation of 25(OH)D3 to 1,25(OH)2D3 in chicks [11, 13,14] and rats [15,16].…”
mentioning
confidence: 99%
“…The initial positive response in BW gain to HRP may be explained by some positive effect of the small amount of F in the diet (or perhaps some other contaminant in the HRP). One possible cause is from the well-known ability of fluoride to replace the OH − ion in hydroxyapatite in bone to form fluorapatite, a stronger, more stable constituent (Zipkin, 1970;Chan et al, 1976;Merkley and Miller, 1983;Huyghebaert et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Sullivan et al (1994) and Summers (1995) concluded that impurities like F could reduce the P utilization from rock phosphate compared with its pure form DCP. Fluorine is not considered to be an essential nutrient for poultry and is usually ignored by the poultry industry, yet indications exist that small quantities of dietary F can improve bone quality and improve overall performance of broilers (Zipkin, 1970;Chan et al, 1976;Merkley and Miller, 1983;Huyghebaert et al, 1988). In some countries, rock phosphate is processed for removing impurities, which further enhances its P utilization and reduces the risk of toxic minerals in finished feed.…”
Section: Introductionmentioning
confidence: 99%
“…Cohen et al [40] have suggested that the magnesium malabsorption found in 12 of 20 of their osteoporotic patients may account for this magnesium deficiency state [40], Lowered bone magnesium content has been reported in diabetes [32,36] and in otosclerotic bone [41]. Increased magnesium levels have been reported in human fluorotic bone [42,43] and in quail [44] and chick [45,46] studies. However, when fluoride-supplemented animals are placed on a low-magnesium diet, bone magnesium de creased [47], Early work by Pellegrino and Biltz [48] showed no difference in magnesium content between control sub jects and patients with renal disease of less than 2 or more than 2 years.…”
Section: Magnesium and Bone Diseasementioning
confidence: 99%